Financing the Global Benefits of Forests : The Bank's GEF Portfolio and the 1991 Forest Strategy - Campbell, J. Gabriel (Washington, DC: World Bank, 2013)
This evaluation was conducted jointly by the Operations Evaluation Department (OED) and Global Environment Facility (GEF). It examines the degree to which Global Environment Facility (GEF) policies are compatible with the World Bank's Forest Strategy. It highlights a number of GEF-specific issues that are significant to forests and to the impact of the World Bank's GEF-funded forest sector portfolio from 1991 to June 1999. The report recommends developing policies and projects that more effectively work with sustainable forest use and management to incorporate conservation objectives, as well as expanding forest strategy goals into the private sector forest industry. The study advises that the World Bank's partnership with the GEF for sustainable conservation of the world's forest biodiversity be expanded, with more strategically developed and realistic goals and more innovative approaches.